The study of symbol in Herman Melville’s Moby Dick - Khosyatillah, Khosyatillah (2008)
This study talks about the discussion of symbolism in Herman Melville’s Moby Dick. Moby Dick is one of Melville’s novels, which contains a large number of symbols that has attracted many readers to analyze. Moby Dick is the story tells about the adventures of Ishmael, who sails on the whaling ship called Pequod, under Captain Ahab’s command. Ishmael firstly believes that he has signed onto a normal whaling vessel, but then he soon knows that Ahab is actually obsessed with the chasing of a white whale that maimed him rather than guiding the ship in the simple pursuit of commerce. He is seeking one specific whale named Moby Dick, a great white whale which is infamous for his giant size and his ability to destroy the whalers who seek him. Captain Ahab begins to dislike and eventually loathe the white whale, when it costs Ahab his leg and his ship. Ahab’s madness at the whale can only end with the death of the whale. All Pequod’s crews die except Ishmael who alone survives by using Queequeg’s coffin, and he becomes the narrator of this story. As the matter of fact, Moby Dick is transformed from an adventure story of a whaling ship voyage into such a symbolic story, which has a more symbolical meaning. This novel is considered as Melville’s masterpiece consisting of many significant symbols, thus, the researcher attempts to analyze it by using semiotic approach. In this case, the researcher conducts two problems of study; they are: what kinds of symbols are found in Melville’s Moby Dick, and what the meanings of each symbol are. Semiotic approach is an approach that studie of sign process (semiosis), or signification and communication, signs, and symbols. This approach is used to analyze symbols in Melville’s Moby Dick by applying Charles Sanders Pierce’s theory of symbols. The analysis is only focused on some characters and objects available in the novel. Moreover, the result of this study finds that some symbols based on characters and objects are included in the kind of cultural symbol and private symbol. Some ...